2023
DOI: 10.47814/ijssrr.v6i9.1489
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Challenges Related to Cultural Diversity Management Within Schools in South Africa

Nkosana Sibanda,
Brian Kwazi Majola

Abstract: Globalization, internationalization and technology have increased the movement of people from different cultural backgrounds around the world. The coexistence has created rapid cultural diversity challenges, forcing many democratic countries to review their labour laws, compelling organisations to adopt sound diversity management policies. Pre 1994 in South Africa, the workforce did not represent the diversity of the country. The end of apartheid created opportunities for culturally diverse workforces in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…As highlighted by Chauke and Goosen (2020), constrained access to resources such as textbooks, library facilities, and modern educational technology impedes learners' learning experiences and their capacity to acquire knowledge. Sibanda and Majola (2023) observed that the scarcity of textbooks in rural schools directly affects learners' access to essential reading materials, which are crucial for studying and understanding the curriculum. Chikoko and Mthembu (2021) highlighted the lack of library facilities in rural schools, which deprives learners of opportunities for independent learning, research, and exploration beyond the classroom.…”
Section: Literature Review Lack Of Instructional Resourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…As highlighted by Chauke and Goosen (2020), constrained access to resources such as textbooks, library facilities, and modern educational technology impedes learners' learning experiences and their capacity to acquire knowledge. Sibanda and Majola (2023) observed that the scarcity of textbooks in rural schools directly affects learners' access to essential reading materials, which are crucial for studying and understanding the curriculum. Chikoko and Mthembu (2021) highlighted the lack of library facilities in rural schools, which deprives learners of opportunities for independent learning, research, and exploration beyond the classroom.…”
Section: Literature Review Lack Of Instructional Resourcesmentioning
confidence: 99%
“…These teachers may lack subject knowledge, pedagogical skills, and classroom management abilities, further exacerbating the academic challenges faced by learners in rural areas. Research by Sibanda and Majola (2023) suggested that the lack of qualified teachers in rural high schools can lead to learner disillusionment and a decrease in their aspirations. Learners might perceive the scarcity of quality education as a barrier to their prospects, leading to decreased motivation to excel academically (Arinaitwe & Corbett, 2022).…”
Section: Teacher Shortagesmentioning
confidence: 99%
See 3 more Smart Citations